2019
DOI: 10.1111/ejss.12864
|View full text |Cite
|
Sign up to set email alerts
|

Soil type and land use effects on tensorial properties of saturated hydraulic conductivity in northern Germany

Abstract: Long‐term soil management can produce anisotropic impacts on soil structure, resulting in differences in horizontal and vertical hydraulic conductivity. As limited data exist on these impacts, this study provides a broad‐scale assessment across 764 soil profiles under arable and grassland use in northern Germany (Federal State: Schleswig‐Holstein). The soils were sampled in the four geological regions: Weichselian glacial region, the sandy outwash region (Lower “Geest”), the Saalian glacial region (Higher “Gee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Three soils varying in soil texture were collected from the following three geological regions of Schleswig-Holstein, Germany: (1) the sandy outwash region (Geest, the outwash region is dominated by Brunic Arenosols or Cambisols, Podzols and Gleysols, as well as Histosols), (2) the Weichselian glacial region in the east (Östliches Hügelland, the Weichselian glacial deposits contain very fertile Luvisols, Cambisols, Anthrosols derived from colluvic material, Gleysols and Rheic Histosols), and (3) the marshland with alluvial deposits in the west (Marsch, the marshland includes different types of Fluvic Gleysols and Histosols) [18]. The selected soils represent the major soil types or climatic zones of the state of Schleswig-Holstein.…”
Section: Collection Preparation and Characterization Of Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Three soils varying in soil texture were collected from the following three geological regions of Schleswig-Holstein, Germany: (1) the sandy outwash region (Geest, the outwash region is dominated by Brunic Arenosols or Cambisols, Podzols and Gleysols, as well as Histosols), (2) the Weichselian glacial region in the east (Östliches Hügelland, the Weichselian glacial deposits contain very fertile Luvisols, Cambisols, Anthrosols derived from colluvic material, Gleysols and Rheic Histosols), and (3) the marshland with alluvial deposits in the west (Marsch, the marshland includes different types of Fluvic Gleysols and Histosols) [18]. The selected soils represent the major soil types or climatic zones of the state of Schleswig-Holstein.…”
Section: Collection Preparation and Characterization Of Soilmentioning
confidence: 99%
“…Different results have been reported by previous researchers regarding the relative efficacy of NIs in varying textured soils. Barth et al [18] found that NIs are more efficient in light soils than heavy soils, whereas Akiyama et al [34] found that the effectiveness of NIs was relatively consistent across the various soil types. According to Fisk et al [35], the efficacy of DMPP and DCD diminished with the addition of soil organic matter, and Marsden et al [36] reported decreased efficacy with higher clay content.…”
Section: Effect Of Nismentioning
confidence: 99%
“…The influence of long‐term soil management (arable and grassland use) on soil structure and related anisotropy properties of representative subsoil horizons in Schleswig‐Holstein was investigated by Horn et al. (2019). They demonstrated that the horizontal anisotropy of hydraulic conductivity is not only soil type‐ and horizon‐dependent, but also more pronounced in arable than in grassland subsoils.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the horizontal anisotropy of hydraulic conductivity is not only soil type‐ and horizon‐dependent, but also more pronounced in arable than in grassland subsoils. Compaction‐induced structural damages in arable soils are primarily attributed to the soil below ploughing depth (≤ 40 cm depth), whereas grassland sites were more affected in the topsoil (Horn et al., 2019). Compared to topsoil compaction, which is almost reversible by tillage, subsoil compaction persists over the long term, because its recovery takes decades (Alakukku et al., 2003; Berisso et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation